2020
DOI: 10.1186/s12884-019-2706-8
|View full text |Cite
|
Sign up to set email alerts
|

Midwives’ engagement in smoking- and alcohol-prevention in prenatal care before and after the introduction of practice guidelines in Switzerland: comparison of survey findings from 2008 and 2018

Abstract: Background: Evidence suggests that cigarette smoking and alcohol consumption during pregnancy negatively impacts fetal health. Health agencies across countries have developed specific guidelines for health professionals in perinatal care to strengthen their role in smoking and alcohol use prevention. One such example is the "Guideline on Screening and Counselling for prevention of cigarette smoking and alcohol consumption before, during, and after pregnancy" introduced by the Swiss Midwives Association in 2011… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Indeed, several studies indicate that health professionals give discordant advice to pregnant and breastfeeding women, from strict abstinence to tolerating low occasional consumption [ 22 , 23 ]. Many authors therefore recommend consistent information about the effects of alcohol consumption on the developing baby as well as education for health care professionals to improve their counselling skills [ 14 , 24 27 ]. Information and counselling about alcohol consumption seems to be widely accepted by pregnant and non-pregnant women [ 28 ] and there is a clear need to address this topic in routine antenatal and postnatal care [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several studies indicate that health professionals give discordant advice to pregnant and breastfeeding women, from strict abstinence to tolerating low occasional consumption [ 22 , 23 ]. Many authors therefore recommend consistent information about the effects of alcohol consumption on the developing baby as well as education for health care professionals to improve their counselling skills [ 14 , 24 27 ]. Information and counselling about alcohol consumption seems to be widely accepted by pregnant and non-pregnant women [ 28 ] and there is a clear need to address this topic in routine antenatal and postnatal care [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Effective smoking cessation treatment requires addressing barriers to quitting and provision of counseling at regular intervals for women who smoke throughout the course of pregnancy and into the postpartum period, as well as support for pharmacotherapy for those with high nicotine dependency or those who are unable to quit with counseling alone. It is important for health care professionals, especially midwives and obstetricians, to be prepared and use the latest evidence‐based treatment for smoking cessation in maternity care settings 53,54 . Moreover, through building trusting and supportive relationships, midwives and other maternity care providers can play an important role in facilitating smoking cessation among pregnant and postpartum women.…”
Section: Discussionmentioning
confidence: 99%
“…It is important for health care professionals, especially midwives and obstetricians, to be prepared and use the latest evidence-based treatment for smoking cessation in maternity care settings. 53,54 Moreover, through building trusting and supportive relationships, midwives and other maternity care providers can play an important role in facilitating smoking cessation among pregnant and postpartum women.…”
Section: Discussionmentioning
confidence: 99%
“…31 A Swiss study further found that while midwives were more aware of the risks of alcohol use in pregnancy following the release of national guidelines, their knowledge and engagement with more extensive prevention strategies remained limited. 32 A Canadian study found that 90.9% of practitioners used of other guidelines related to alcohol use in pregnancy either as a standalone or alongside national guidelines. 28 However, several studies also reported enablers to guideline adherence.…”
Section: Level 2 Preventionmentioning
confidence: 99%